Service Experience Perspectives in Ghanaian Private Universities - Bernard, Tutu-Boahene; Divine Mawuli, Akwensivie (British Journal of Marketing Studies, 2014)
Service experiences are not only defined in terms of human interactions (service providers, consumers/customers and co-consumers), but also the interaction between individuals and self-service technology, and various tangible elements within the service environment. It is argued that the outcome of such encounters impacts on student experiences of service quality in tertiary education. This study thus seeks to examine the relationships that exist between student experiences and service quality indicators using Gummesson’s 4Q model of delivering quality. Empirical data gathered from 700 students of three private universities in Accra, Ghana was analyzed to assess the extent to which service quality indicators could influence students’ experiences in these universities. The discussion in this paper is thus predominantly fieldwork-based, using a combination of primary and secondary sources to generate relevant data to analyze the relationship between service experience and student service quality indicators. The finding indicates a positive but insignificant relationship between student experiences and service quality indicators. Thus the finding suggests that service quality indicators such as input quality, process quality, interactive quality and outcome quality impact on service experiences during service encounter. The implications of this finding to the management of tertiary education in Ghana are discussed and suggestions for further research are made